The network organizational chart as a tool for managing organizational complexity - Aita Ramírez Gastón, Rafael Martín Antonio (2016)
Companies in the twenty first century are required to continually adapt to an uncertain and ever-changing environment, which requires a more organic and flexible organization, without losing the benefits of volume production and economies of scale. The Organizational Network is a tool that allows the company to study the channels through which materials, money, and information resources flow between jobs, unlike the traditional Organizational Chart that only shows the hierarchy of power. Analyzing these links like a complex network will allow the manager to identify bottlenecks and agglomerations of power and measure the entropy generated in the organization. This gives a quantitative measure of the complexity of the business and, therefore, both its organic growth and efficient growth can be managed.